Effect of Emotional Intelligence and Religiosity to Prosocial Behavior in College Students - ., Mujidin; Rustam , Husnul Khotimah; Aji , Ilham Setyo (Journal of Ecohumanism, 2024)
Purpose: Honesty is essential in all fields of life, including education. Based on our preliminary findings, students are typically dishonest and ignorant of others. This statement is accordance with our research objective to determine whether emotional intelligence influence students prosocial behavior. Design/methodology/approach: We targeted a suitable sample, namely 132 Psychology undergraduate students selected through random cluster sampling. The students filled out three scales: the prosocial scale, the emotional intelligence scale, and the religiosity scale. The prosocial scale and emotional intelligence reliability are 0.948 and 0.920, respectively. The religiosity scale, on the other hand, has a reliability of 0.955. Findings: This study's results indicate a significant relationship between emotional intelligence, religiosity, and prosocial behavior. We conclude that emotional intelligence and religiosity are significantly related to prosocial behavior. The practical contribution of emotional intelligence and religiosity to prosocial behavior is 68.97%. Specifically, emotional intelligence contributed 10.53% and religiosity contributed 58.44%. Research limitations/implications (if applicable): Emotional intelligence helps students become more sensitive and open with other people, which leads to a strong desire to rise with one another. Religiosity also has a significant impact when students increase their belief in God. Practical implications (if applicable): This study specifically explores the positive prosocial behavior that can be assisted by emotional intelligence and religiosity. Future studies can expand this research's discussion by exploring the negative side of prosocial under different conditions.